The new economic policy of Kazakhstan “Nurly Zhol” in the context of mutual synergy with the program “One belt – one way” of China - Aldabek, N. (Journal of Oriental Studies, 2024)
This article analyzes the relations between two countries in the context of mutual synergy of the new economic policy of Kazakhstan and China. Analyzed the effectiveness of the current economic and trade relations and predicted new horizons of mutual beneficial relations. Characterized modern relationship between China and Kazakhstan, and also is given analysis of inter-state relations in the context of the revival of the Silk Road. There mutually side of the Chinese leadership initiative “The Economic Belt of the Silk Road” for Kazakhstan and the importance of Kazakhstan’s policy to attract Chinese investment to diversify own economy.